Pengaruh Model Pembelajaran Kooperatif Tipe Talking Stick Terhadap Hasil Belajar Siswa Pada Pembelajaran Tematik Kelas V Sekolah Dasar Negeri Kota Bengkulu - Sakinah Gita Utami; Nani Yuliantini; Hasnawati Hasnawati (Universitas Bengkulu, 2020)
This research to determine the effect of the Talking Stick Cooperative Learning Model on Student Learning Outcomes in Thematic Learning Class V of Bengkulu City Primary School. Types of research is quantitative. Research method is experimental. The design in this study is “The Matching Only Pretest-Posttest Control Group Design”. Population in this study is all students class V of elementary school Bengkulu City that applies the 2013 curriculum and accreditation A. The study sample was taken using the Random Sampling Cluster technique, so that the VA class SDN 71 Bengkulu city was obtained ad an experimental class and the VA Class SDN 103 Bengkulu city as control class. The research instrument used in the form of cognitive learning test result in the form of multiple choice provided through pretest and posttest in the experimental class and the control class. Data analysis technique in this research is quantitative analysis using descriptive statistics and infertial statistics. From the result of the study note the result of the t-test obtained tcound of Indonesian subjects at 4.37 and on natural science subjects at 4.81 with a ttable at a significant level of 5% of 2.00 where tcount is greater than ttable. From these data in appears that there are differences in learning outcomes achieved by student in the experimental and control classes. Thus it can be concluded that there is a significant effect on student learning outcomes in Thematic learning that uses the Talking Stick type of cooperative learning model.